(untitled) (GEON Journal (Management, Organizations and Business), 2026)
Problem Statement. This study addresses a critical gap in the Ecuadorian science and technology system: the weak connection between research activities carried out at universities and the effective generation of knowledge-based businesses. In particular, it aimed to diagnose the level of entrepreneurial intention among active research staff at the State Polytechnic University of Carchi (UPEC) between 2015 and 2020. Objective. This research aims to determine the entrepreneurial intentions of researchers at the State Polytechnic University of Carchi (UPEC) who conducted research activities between 2015 and 2020. Materials and Methods. Entrepreneurial intention was measured from three perspectives: scientific profile, demographic profile, and entrepreneurial profile. To achieve this objective, a 93-item questionnaire, validated by experts in the field, was developed and administered to a sample of 30 individuals, including research professors, administrators, and authorities of the Higher Education Institution. The sampling method used was purposive and non-probabilistic. Results. Among the main findings, a medium level (57.74 out of 100) in the entrepreneurial intention of UPEC researchers stands out. The profile that contributed most to this result was the entrepreneurial profile (66%), followed by the scientific profile (47%). Discussion. Although there is great entrepreneurial and scientific potential among researchers, their capacity to initiate and manage ventures needs improvement to enhance the quality and impact of research results. Conclusions. Finally, generating institutional support, spaces, and incentives is key, as is strengthening support networks alliances with the productive, public, and private sectors, and a leading role for academia in shaping the regional entrepreneurship and innovation ecosystem. Contribution/Originality. There is very little research on entrepreneurial intention applied to university researchers in Ecuador. We hope to contribute to this knowledge base, motivate innovation and technology transfer, and foster the development of science- and technology based ventures in Ecuadorian higher education institutions.